2021
DOI: 10.3389/fimmu.2021.739768
|View full text |Cite
|
Sign up to set email alerts
|

m6A Methylation Modification Patterns and Tumor Microenvironment Infiltration Characterization in Pancreatic Cancer

Abstract: Recent studies have shown that RNA N6-methyladenosine (m6A) modification plays an important part in tumorigenesis and immune-related biological processes. However, the comprehensive landscape of immune cell infiltration characteristics in the tumor microenvironment (TME) mediated by m6A methylation modification in pancreatic cancer has not yet been elucidated. Based on consensus clustering algorithm, we identified two m6A modification subtypes and then determined two m6A-related gene subtypes among 434 pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
(116 reference statements)
2
13
0
Order By: Relevance
“…Accumulating evidence suggests that m6A modification plays pivotal roles in carcinogenesis, innate immunity, and anti-tumor immune response ( He et al, 2019 ; Gu et al, 2021 ; Uddin et al, 2021 ). Recently, the role of m6A modification patterns in TME infiltration characterizations has been comprehensively elucidated in other solid tumors ( Zhang et al, 2020 ; Chong et al, 2021 ; Du et al, 2021 ; Li et al, 2021 ; Sun et al, 2021 ). In this study, we explored the correlation between m6A modification and TME cell infiltration in ccRCC to enhance our apprehension of TME anti-tumor immune response and identify more effective immunotherapy strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence suggests that m6A modification plays pivotal roles in carcinogenesis, innate immunity, and anti-tumor immune response ( He et al, 2019 ; Gu et al, 2021 ; Uddin et al, 2021 ). Recently, the role of m6A modification patterns in TME infiltration characterizations has been comprehensively elucidated in other solid tumors ( Zhang et al, 2020 ; Chong et al, 2021 ; Du et al, 2021 ; Li et al, 2021 ; Sun et al, 2021 ). In this study, we explored the correlation between m6A modification and TME cell infiltration in ccRCC to enhance our apprehension of TME anti-tumor immune response and identify more effective immunotherapy strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, principal component analysis (PCA) was conducted to establish an m6A-associated gene signature, and principal components 1 and 2 were used for serving as signature scores. Consistent with previous studies ( Zhang et al, 2020 ; Chong et al, 2021 ; Sun et al, 2021 ), an m6A score was defined for the individual sample using the following formula: m6A score = ∑(PC1i + PC2i), where i indicates the expression value of the i th m6A phenotype-related gene. Additionally, we investigated the prognostic significance and associations between the m6A score and TME characteristics and further verified the results in the GSE22541 ccRCC cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we analyzed the correlation of 51 genes [21] encoding immunomodulatory molecules with risk scores and found that these genes were highly expressed in most of the high-risk patients. The application of PD-1 or PD-L1 monoclonal antibodies and anti-PD-1/PD-L1 antibody combination therapy have greatly advanced the process of immunotherapy [40].The work of Sun M [12] showed that the expression of PD-L1 and PD-1 was positively correlated with the m6A score. While PD-1 and PD-L1 are highly expressed in the high-risk group, our epigenetic results indicate that most m 6 A regulators are highly expressed in the high-risk group, and combining these two results, we conclude that the expression of PD-1 and PD-L1 is positively correlated with PCFG scores.…”
Section: Discussionmentioning
confidence: 99%
“…M 6 A methylation modi cation is a dynamically reversible modi cation process that is mainly regulated by m 6 A methyltransferase complexes (writers) such as METTL3, m 6 A demethylases (erasers) such as ALKBH5, and m 6 A binding proteins (readers) such as YTHDC1 [11]. Recently, it has been shown that m 6 A plays an important role in the tumor immune microenvironment (TIME), providing new ideas for clinical immunotherapy [12,13]. However, the m 6 A level and TIME in digestive system pancancer patients with a high incidence of venous thrombosis remain ambiguous.…”
Section: Introductionmentioning
confidence: 99%